A medieval physician: Amirdovlat Amasiatsi (1420–1495). (May 2019) - Gurunluoglu, Aslin; Gurunluoglu, Raffi; Hakobyan, Tatevik
We aimed to acquaint the reader with a medieval physician, Amirdovlat Amasiatsi, who lived and practiced in the 15th century Anatolia. Amirdovlat wrote several books on medicine mainly focusing on phytotherapy and pharmacology using medicinal plants, animal-derived products and minerals. All his works were written in Middle Armenian, spoken Armenian language of the time. In his writings, Amirdovlat described unique recipes that represent a portrayal of medical knowledge and practice at the time in Anatolia where he lived and worked. He discussed the physical and therapeutic properties as well as geographic distributions of various plants and minerals, using different languages, mainly Turkish, Greek, Arabic, French and Persian. Amirdovlat's works not only enhanced our understanding of Armenian medical practices but also provided great deal of information on those of Ancient Greco-Roman as well as Islamic world, demonstrating close relationship of Armenian medicine with Greco-Roman and Islamic medicine. Amirdovlat accomplished this by amalgamating the past and contemporary practices of his time. In this regard, Amirdovlat's works, in particular "Useless for the Ignorant", are very unique playing a significant role in preserving traditions and heritage of different cultures.